Alih Kode dan Campur Kode dalam Film Cinta dalam Ikhlas Karya Fajar Bustomi: Code Switching and Code Mixing in the Film Love in Ikhlas by Fajar Bustomi - Septian, Ahmad Arif; Yuda S, Dendi; Rohanda, Rohanda (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
This study aims to reveal the forms and functions of code-switching and code-mixing in the film Cinta dalam Ikhlas by Fajar Bustomi using a qualitative approach and descriptive-analytical methods. The formal object of this study is the linguistic phenomenon of code-switching and code-mixing. In contrast, the material object is the film Cinta dalam Ikhlas, which narratively displays the reality of a multilingual society in Indonesia's urban religious context. This film was chosen because it reflects the socio-linguistic dynamics of modern society, which often switches languages in informal and formal situations. Based on the results of this study, it can be concluded that all forms of code-switching and code-mixing found are included in the external category, marked by the presence of switching and insertion of foreign languages, especially Arabic and English, and also Javanese and Sundanese regional languages ?? including internal languages, into the main language, namely Indonesian. The researcher found thirty-two linguistic data, consisting of five external code-switching data and twenty-seven code-mixing data, that appeared in words, phrases, and idiomatic expressions. These findings reflect linguistic practices that not only function as a means of communication but also as a symbol of religious identity, an expression of interpersonal affection, and a reflection of global culture that helps construct the characters, values, and narrative contexts in the film in a holistic and representative manner.